Effectiveness of a Singaporean Community-Based Physical Activity and Nutrition Intervention: A Cluster Randomized Controlled Trial - Wong, Elaine Yee-Sing; James, Tony; Lee, Andy; Jancey, Jonine (2020)
This study examined the effectiveness of a 6-month intervention to improve the health behaviors and outcomes among women aged 50 years and older. A sample of 580 (intervention n = 295; control n = 285) women was recruited from 26 recreational centers. Only the intervention group participated in the Singapore Physical Activity (PA) and Nutrition Study (SPANS), received health resources (calendar, recipe, and booklets) and motivational support from program ambassadors. The intervention group showed significant improvements in moderate-intensity PA, vigorous-intensity PA, and total PA (P <.001), increased intake frequency of fruit and vegetables (P =.049), a reduction in salt and sugary beverage intake (P ≤.042), and reductions in systolic blood pressure (BP; −3.68 mm Hg), diastolic BP (−3.54 mm Hg), and percentage body fat (−2.13%; P ≤.020) when compared with the control group. The SPANS appeared to be efficacious in improving PA and dietary behaviors, reducing BP and percentage body fat among Singaporean women.